Knowledge, Attitudes and Practice toward the Disposal of Unused Expired Medicines and Associated Factors: A Cross-Sectional Survey in Yogyakarta Primary Health Care - Woro Supadmi; Devi Indri Alvian; Larasati Aprita Nanda Setyawan; Della Friska Andani; Muhammad Muhlis; Muhammad Thesa Ghozali (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: The accumulation and inappropriate disposal of unused and expired drugs lead to significant risks to public health and the environment. Unsafe disposal behaviors contribute to the water and soil contamination and increase the potential for drug misuse. Recognizing community knowledge, attitudes, and practices (KAP) is essential for developing effective health promotion strategies to improve pharmaceutical waste management at primary care level. This study primarily aimed to assess the public’s KAP toward disposal of unused and expired drugs and its implications for health promotion in Indonesian primary health care settings. Methods: A cross-sectional survey was conducted among 358 participants selected through purposive sampling at Banguntapan II, Danurejan II, and Mlati II primary healthcare centers in the Special Region of Yogyakarta, Indonesia. Data were technically collected using a prior validated questionnaire. Descriptive statistics, Chi-square tests, Spearman correlation and multivariate logistic regression were used to analyse data. Results: 89.3% of participants reported they had unused or expired drugs stored in their home, and the main reason for storage was better health (52%) or excess medicine (43%). Although 64% have reported excellent knowledge and 98.3% positive attitudes, only 27.7% practiced proper disposal. (p < 0.05) Knowledge and attitudes were significantly influenced by, education income and medical history In addition, knowledge and attitude were significantly associated with disposal practices (p < 0.05). Conclusion: While public awareness, understanding and attitude were favorable, there are deficiencies in disposal practices. The implementation of pharmacist-led education, drug take-back programs and primary care services for health promotion should be strengthened in the community to raise awareness of CS use, reduce inappropriate disposal practices and protect public health through improved environmental conditions.